Regulation of soybean drought response by mepiquat chloride pretreatment - Wang, Xiyue; Zhou, Xinyu; Qu, Zhipeng; Yan, Chao; Ma, Chunmei; Liu, Jun; Dong, Shoukun (Frontiers in Plant Science, 2023)
Soybean is the world's most important cultivated crop, and drought can affect their growth and, eventually, yields. Foliar application of mepiquat chloride (DPC) can potentially alleviate the damage caused by drought stress in plants; however, the mechanism of DPC regulation of soybean drought response has not been studied. Thus, this study investigated the mechanism of soybean drought response regulation by mepiquat chloride in two varieties of soybean, sensitive Heinong 65 (HN65) and drought-tolerant Heinong 44 (HN44), under three treatment scenarios, normal, drought stress, and drought stress + DPC conditions. DPC promoted dry matter accumulation under drought stress, reduced plant height, decreased antioxidant enzyme activity, and significantly decreased malondialdehyde content. The light capture processes, photosystems I and II, were inhibited; however, accumulation and upregulation of several amino acids and flavonoids by DPC was observed. Multi-omics joint analysis indicated 2-oxocarboxylic acid metabolism and isoflavone biosynthetic pathways to be the core pathways by which DPC regulated soybean drought response. Candidate genes such as LOC100816177, SOMT-2, LOC100784120, LOC100797504, LOC100794610, and LOC100819853 were identified to be crucial for the drought resistance of soybeans. Finally, a model was constructed to systematically describe the regulatory mechanism of DPC application in soybean under drought stress.